Canadian Foreign Aid and the Christian Right: Stephen Harper, Abortion, and the Global Culture Wars in Sub-Saharan Africa, 2006-2015 - Jex, Erin (Université d'Ottawa / University of Ottawa, 2017)
This thesis expands upon the concept of the global culture wars in sub-Saharan Africa from a Canadian perspective, focusing on the growing division within Canada between conservative, religious values and liberal, progressive ones (Caplan, 2012). This division led to a political and cultural realignment alongside the increased visibility and leadership of religious and faith communities in Canadian public and political life. Amidst this polarization, Conservative Party leader Stephen Harper was elected Prime Minister in February 2006. Under his leadership, a conservative, pro-family agenda was established. This agenda, which advocates a traditional understanding of family life and structure, in particular refers to a legally married, heterosexual couple with children. It was supported by the evangelical Christian population in Canada, which grew from a united religious community in Canada into a significant constituency of the Conservative Party. Harper’s tenure, coupled with the increased visibility and leadership of faith and religious communities significantly affected domestic and international policies during his tenure as Prime Minister, from 2006 to 2015. This thesis examines the Muskoka Initiative on Maternal, Child, and Newborn Health (Muskoka-MNCH) and shows how this initiative, which fostered anti-abortion rhetoric abroad, was utilized to appease the evangelical community’s anti-abortion position in Canada.
Keywords: Stephen Harper; Conservative Party; Canadian Christian Right; The Global Culture Wars; Sub-Saharan Africa; Religion in Politics; Evangelicalism in Canada; Abortion; Foreign Aid; The Muskoka Initiative